Capacity Building in the Sweetpotato Weevil Resistance Research Component - International Potato Center (2014)
The development of transgenic sweetpotato with gene(s) for resistance to the African sweetpotato weevils Cylas puncticollis and C. brunneus involves generation, testing and promotion of the new sweetpotato varieties and requires the active participation of scientists, opinion-and decision–makers in the country where these varieties are developed. Our vision is to build capacity so that there is the ability to adapt and develop technologies in the country where it will be adopted. Introduction of this technology has involved the establishment of facilities in Kenya and Uganda where the work was to be carried out, building practical knowledge and communication skills of the personnel involved and the development of the new varieties. Three doctoral students have been trained under this program.